2014
DOI: 10.3892/mmr.2014.2301
|View full text |Cite
|
Sign up to set email alerts
|

Activated δ-opioid receptors inhibit hydrogen peroxide-induced apoptosis in liver cancer cells through the PKC/ERK signaling pathway

Abstract: Apoptotic liver cancer cells have important roles in liver tumorigenesis and liver cancer progression. Recent studies have shown that δ‑opioid receptors are highly expressed in human liver and liver cancer cells. The present study aimed to investigate the role of activated δ‑opioid receptors on human liver cancer cell apoptosis and its interrelation with the mitochondria and the protein kinase C/extracellular‑signal‑regulated kinase (PKC/ERK) signaling pathway. H2O2 was used to induce apoptosis in human liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
2
13
1
Order By: Relevance
“…DOR activation inhibits serum deprivation-induced apoptosis via the activation of PKC and the mitochondrial pathway in human liver cells [63]. DOR activation inhibited mitochondria-mediated apoptosis in liver cancer cells through the PKC/ERK signaling pathway [64], which is consistent with the observation made in neuronal cells [60, 62]. Apparently, DOR actively participates in the regulation of hepatic cell survival.…”
Section: Discussionsupporting
confidence: 66%
“…DOR activation inhibits serum deprivation-induced apoptosis via the activation of PKC and the mitochondrial pathway in human liver cells [63]. DOR activation inhibited mitochondria-mediated apoptosis in liver cancer cells through the PKC/ERK signaling pathway [64], which is consistent with the observation made in neuronal cells [60, 62]. Apparently, DOR actively participates in the regulation of hepatic cell survival.…”
Section: Discussionsupporting
confidence: 66%
“…The SMAC-mediated mitochondrial apoptotic pathway plays a key regulatory role in the development and progression of malignancies such as breast cancer [27], prostate cancer [28], and liver cancer [29]. Our study showed that downregulation of HSF1 promotes both SMAC expression and apoptosis in pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 75%
“…However, we were unable to detect the altered BCL-xL expression in HCC after modulating Pinin expression (data not shown), indicating that other molecules or signaling pathways may contribute to Pinin's effects. Indeed, the phosphorylation status of ERK1/2 that are key molecules in MAPK pathway and well known for the growth promotion and anti-apoptotic effects in HCC, was associated with Pinin expression in GD treated HCC cells [27]. It was clear that ERK activation gradually disappeared with GD treatment in 24 h. However, in Pinin depleted cells this effect was further accelerated as it was shown that ERK phosphorylation reduced more rapidly at 12 h after GD treatment.…”
Section: Discussionmentioning
confidence: 99%